Quality Management of Learning in An Effort to Improve Students' Learning Achievement in Open High School - R. Eman Sulaeman (International Journal of Nusantara Islam, 2021)
This research is motivated by the existence of an interesting phenomenon in the quality management of learning in open high school . M engacu on learning outcomes based on the value Exams (US) on the open schools there are differences yan significant value. The School Examination (US) scores obtained by Open High School students are generally lower than the School Examination (US) scores of regular High School students. It became an Indic ator be l um optimal quality of learning developed by the manager of SMA Open. The focus of this research is the management of the quality of learning in an effort to improve student achievement at the Open High School . This research is a kind of qualitative research with descriptive method which was conducted at Sukasari Open High School, Purwakarta Regency and East Telukjambe Open High School, Karawang Regency . Data collection techniques combine field observations, interviews and documentation studies. The grand theory of this research uses the quality management theory of Edward W. Deming . Inductive data analysis resulted in some conclusions, namely: in umu m management of the quality of learning in an effort to improve student achievement in the Sukasari Open High School, Purwakarta Regency and the East Telukjambe Open High School, Karawang Regency, it has not run optimally. In particular: (1) Planning ( Plan ) for the quality of learning in improving student achievement has been successfully implemented with its own characteristics and uniqueness; (2) Implementation ( Do ) of learning quality in improving the learning achievement of Open High School students using tutors as the spearhead of the implementation of quality learning carried out in each Learning Activity Place (TKB) ; (3) Control, Supervision, Evaluation and Revision ( Check ) the quality of learning in improving the learning achievement of Open High School students is carried out simultaneously with the implementation stages ; (4) T ahapan follow-up management of the quality of learning in improving student achievement SMA Open has been done; (5) The factors supporting and learning quality management in improving learning achievement in high school Open school come from both internal and from the external school ; and (6) Future solutions and improvements that can be made in the management of learning quality in improving the learning achievement of Open High School students include introducing and cultivating a culture of quality in each school.